Zasady regulujące pobór rekrutów polskich do armii pruskiej jako element polityki germanizacji 1871–1914 - Jędrysiak, Jacek (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The article presents the circumstances of introducing and changing the regulations of the so-called “dispersal policy” (Ger. Verstreuungspolitik) pursued by the German army towards Polish conscripts until the out break of the First World War. The guidelines introduced in 1872 disbanded regiments composed largely of Poles in the Prussian partition.From then on, Polish recruits were mostly sent to regiments in the German-speaking areas. As a result of the tightening anti-Polish policy of the Prussian authorities in subsequent years, the proportion of conscript levies from Wielkopolska serving in their native prov-ince fell to 10 percent.
p. 39-73
Summary in English.
Keywords: conscription; Prussian partition (Poland) - 1870-1914; Germanisation; Prussian army; Poles; Prussian partition - politics and government; Germanization - Poland - Prussian partition; Polish soldiers - Prussia - 1870-1914; Prussia. Königlich Preussische Armee - minorities